2020
DOI: 10.1101/2020.08.18.253120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cnr2 is important for Ribbon Synapse Maturation and Function in Hair Cells and Photoreceptors

Abstract: The role of the cannabinoid receptor 2 (CNR2) is still poorly described in sensory epithelia. We found strong cnr2 expression in hair cells (HCs) of the inner ear and the lateral line (LL), a superficial sensory structure in fish. Next, we demonstrated that sensory synapses in HCs were severely perturbed in larvae lacking cnr2. Appearance and distribution of presynaptic ribbons and calcium channels (Cav1.3) were profoundly altered in mutant animals. Clustering of membrane-associated guanylate kinase (MAGUK) in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 161 publications
(223 reference statements)
0
1
0
Order By: Relevance
“…However, a recent study in the developing (3-day post-fertilization) zebrafish has shown that Cnr2 is expressed in both the sensory epithelia (SE) of the inner ear and lateral line neuromast. Loss of function of the cnr2 gene resulted in the formation of immature synapses and irregular tethering of ribbons as well as changes in size, shape, and number of the neurotransmitter containing vesicles and resulted in accelerated vesicular trafficking (Colon-Cruz et al, 2020). So far, it remains unknown, whether CB2 activation plays similar roles in rodents or other mammals, but the study is suggestive that ECB signaling could play a critical role in the establishment and maintenance of ribbon synapses in cochlear IHCs.…”
Section: Putative Functions Of Ecb Signaling In Otic Developmentmentioning
confidence: 94%
“…However, a recent study in the developing (3-day post-fertilization) zebrafish has shown that Cnr2 is expressed in both the sensory epithelia (SE) of the inner ear and lateral line neuromast. Loss of function of the cnr2 gene resulted in the formation of immature synapses and irregular tethering of ribbons as well as changes in size, shape, and number of the neurotransmitter containing vesicles and resulted in accelerated vesicular trafficking (Colon-Cruz et al, 2020). So far, it remains unknown, whether CB2 activation plays similar roles in rodents or other mammals, but the study is suggestive that ECB signaling could play a critical role in the establishment and maintenance of ribbon synapses in cochlear IHCs.…”
Section: Putative Functions Of Ecb Signaling In Otic Developmentmentioning
confidence: 94%